Comparison of Atomic Absorption Spectroscopy and Energy Dispersive X-Ray Fluorescence Spectrometer Methods for Chemical Analysis - Eser*, A.; Kahraman, E.; Demiray, M. (Asian Journal of Chemistry, 2014)
This study aims to find out which method can obtained the most accurate results in less time and at the lowest cost on the basis of element. At the beginning of the study, worldwide researches about this subject are investigated. As a result of this investigation, two of the chemical analysis methods which are widely used in the elemental analysis of the inorganic raw materials used in mining were compared. Then, 15 test samples which have different compositions and generally investigated main element content were determined in order to compare. The samples were analyzed in parallel with atomic absorption spectroscopy (AAS) and energy-dispersive X-ray fluorescence spectrometer (EDXRF). The compatibility and the deviations were determined by comparing the results of the analysis statistically from both methods. It was tried to determine which method can be used for which type of elements. It is observed that the material composition effects choosing appropriate method.